2015
DOI: 10.1371/journal.pone.0133495
|View full text |Cite
|
Sign up to set email alerts
|

More Cercospora Species Infect Soybeans across the Americas than Meets the Eye

Abstract: Diseases of soybean caused by Cercospora spp. are endemic throughout the world’s soybean production regions. Species diversity in the genus Cercospora has been underestimated due to overdependence on morphological characteristics, symptoms, and host associations. Currently, only two species (Cercospora kikuchii and C. sojina) are recognized to infect soybean; C. kikuchii causes Cercospora leaf blight (CLB) and purple seed stain (PSS), whereas C. sojina causes frogeye leaf spot. To assess cryptic speciation amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
10

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 40 publications
1
43
0
10
Order By: Relevance
“…Since the studies leading to this outcome are relatively recent, the presence of different genotypes or species within the WCM complex has not yet been accounted for in applied contexts. Such oversights may have serious consequences, as cryptic species or genotypes within species complexes may differ with respect to key biological traits, such as host range, life-history traits, tolerance to abiotic factors, insecticide resistance, and ability to transmit plant viruses [ 12 18 ]. WCM is a complex of at least eight genetic lineages, with host-acceptance traits ranging from polyphagous to highly host-specific [ 9 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the studies leading to this outcome are relatively recent, the presence of different genotypes or species within the WCM complex has not yet been accounted for in applied contexts. Such oversights may have serious consequences, as cryptic species or genotypes within species complexes may differ with respect to key biological traits, such as host range, life-history traits, tolerance to abiotic factors, insecticide resistance, and ability to transmit plant viruses [ 12 18 ]. WCM is a complex of at least eight genetic lineages, with host-acceptance traits ranging from polyphagous to highly host-specific [ 9 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…sigesbeckiae from leaves and Cercospora cf. flagellaris from seeds and leaves ( 1 , 2 ). Prior to 2015, most records of Cercospora cf.…”
Section: Genome Announcementmentioning
confidence: 99%
“…Prior to 2015, most records of Cercospora cf. sigesbeckiae came from Asia ( 3 ), but recent studies also reported this pathogen from Argentina ( 2 ) and Louisiana, USA ( 1 ).…”
Section: Genome Announcementmentioning
confidence: 99%
“…In 2009 and 2010, the disease spread rapidly throughout the main soybean producing areas in Heilongjiang province in China, causing serious losses to soybean production [4]. Further, the disease has dramatically impacted soybean production in the USA and Argentina [5,6].…”
Section: Introductionmentioning
confidence: 99%